ADVANCED METHODS OF ORGANIZING AND MANAGING THE PEDAGOGICAL PROCESS IN GENERAL SECONDARY EDUCATION ON THE BASIS OF AN INNOVATIVE APPROACH - Mamatova Saodat Mahmudovna (Scholar Express Journal, 2022)
The organization of the educational process has become one of the most important areas of training in today's world. It is the introduction of modern technologies in this process that has led to large-scale innovations in the field. That is why today in secondary schools, innovative technologies are used in the education of students. In this article, the author describes in detail the impact and place of pedagogical innovative methods on these processes.
Keywords: pedagogical; modern technologies; innovation; education